Geotextile tubes as submerged dykes for shoreline management in Malaysia - Lee, E.C.; Douglas, R.S. (Geotextiles and geomembranes, 2012)
The shoreline in Malaysia has experienced severe erosion due to the impact of high energy waves, both on the predominantly mud coasts and the predominantly sandy coasts. This perennial process has resulted in the deterioration of the quality of the beach on the sandy coasts and loss of valuable land. Several measures had, in the past, been implemented to mitigate these adverse effects but these had mostly been hard solutions. The application of geosynthetic tubes for shoreline management was introduced in the State of Terengganu on the east coast of Peninsular Malaysia which experiences severe erosion during the North-East Monsoon period. A pilot project, utilising geotextile tubes installed as submerged dykes, was undertaken in 2006 to address the erosion problems and arrest the further erosion of the shoreline at Teluk Kalong, Kemaman, Terengganu. The geotextile tubes comprise of high strength woven geotextile in-filled with sand slurry. Subsequently in 2008, the state implemented a similar shoreline protection project at Pantai Batu Buruk, protecting a 5 km stretch of beach. These works comprise of the installation of 3.5 m diameter geotextile tubes, as submerged dykes, approximately 150 m offshore. The geotextile fabric allows consolidation of the sand to create a long sausage-like gravity structure. Post-installation surveys carried out indicated that the shoreline has improved with much wider foreshore area. Significant sand deposition was also recorded on the foreshore area, which contributes to the long term shoreline management and promoting sustainable protection of the shoreline. This article discusses the concept of shoreline management using geotextile tubes as submerged dykes. The details of these two projects and the outcome of the projects are presented.